Outcome of cataract surgery at one year in Kenya, the Philippines and Bangladesh. Issue 7 (11th February 2009) - Lindfield, R; Kuper, H; Polack, S; Eusebio, C; Mathenge, W; Wadud, Z; Rashid, A M; Foster, A
Abstract : Aims: To assess the change in vision following cataract surgery in Kenya, Bangladesh and the Philippines and to identify causes and predictors of poor outcome. Methods: Cases were identified through surveys, outreach and clinics. They underwent preoperative visual acuity measurement and ophthalmic examination. Cases were re-examined 8–15 months after cataract surgery. Information on age, gender, poverty and literacy was collected at baseline. Results: 452 eyes of 346 people underwent surgery. 124 (27%) eyes had an adverse outcome. In Kenya and the Philippines, the main cause of adverse outcome was refractive error (37% and 49% respectively of all adverse outcomes) then comorbid ocular disease (26% and 27%). In Bangladesh, this was comorbid disease (58%) then surgical complications (21%). There was no significant association between adverse outcome and gender, age, literacy, poverty or preoperative visual acuity. Conclusions: Adverse outcomes following cataract surgery were frequent in the three countries. Main causes were refractive error and preoperative comorbidities. Many patients are not attaining the outcomes available with modern surgery. Focus should be on correcting refractive error, through operative techniques or postoperative refraction, and on a system for assessing comorbidities and communicating risk to patients. These are only achievable with a commitment to ongoing surgical audit.